If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8+3x=6x+2
We move all terms to the left:
8+3x-(6x+2)=0
We get rid of parentheses
3x-6x-2+8=0
We add all the numbers together, and all the variables
-3x+6=0
We move all terms containing x to the left, all other terms to the right
-3x=-6
x=-6/-3
x=+2
| -5+7g=-11+40 | | 6x-(3x-2)=-16 | | 9+7j+j=12+9j | | InI=0 | | 6n+2-10n=22 | | -5+7g=-11g+40 | | -10-7x=2x+4+4 | | 38x=342 | | 3(6k+6)=144 | | 3x+2+7=32 | | 2a+3+2+5a=7a+5 | | 7.5/x=2.5 | | -47=-3x-50 | | 3(x−2)=15 | | −5(3−4x)=−6+20x−9 | | b+38/7=8 | | 14.50-54=d | | 2x-2+7x-3=-50 | | 2/3(c+9)=4 | | y+3-1=5 | | 1+6a=1+8a-2a | | 6x–2(-3x–5)=154 | | 2/3x-1/4=1/3 | | -12+8m=6+6m | | 3(x+2x+9)=18 | | x/5=1.8 | | 3(x-2=x+2 | | 31b-9b+8b=0 | | x+5(x+1)=7 | | -6-6(x-7)=42-6x | | Z+4(z-3)=13 | | d=54 |